A Round Table Devoted to the Early Phase of Pharmaceutical Development was Held in Novosibirsk as a Part of OpenBio-2022 Forum - article Editorial (Разработка и регистрация лекарственных средств)
Experts discussed current opportunities for pharmaceutical development in our country, discussed actual difficulties and the ways for overcoming it.